2015
DOI: 10.4314/ahs.v15i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Psychological wellbeing and biochemical modulation in response to weight loss in obese type 2 diabetes patients

Abstract: Background: Obesity in type 2 diabetes patients is a serious health issue by itself; it is also associated with other health problems including psychiatric illnesses. The psychological effects of dieting and weight loss have been a matter of controversy in the field of obesity management. Objective: The aim of this study was to compare the impact of weight loss because of aerobic exercise training and dietary measures on psychological wellbeing and biochemical modulation in obese type 2 diabetes patients. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…These findings are consistent with previous studies showing that blood-based biomarkers of inflammation and insulin resistance are related to positive affect/happiness (Matsunaga et al, 2011;Steptoe et al, 2008), well-being (Boehm & Kubzansky, 2012;Osama & Shehab Ael, 2015;Phillips & Perry, 2015;Steptoe et al, 2012), optimism (Ikeda et al, 2011;Roy et al, 2010), psychological resilience or 'hardiness' (Fields, Hoyt, Linnville, & Moore, 2015;Sandvik et al, 2013), and perceived stress (Aschbacher et al, 2013;BarbosaÀLeiker et al, 2014;Shimanoe et al, 2014). Although longitudinal research is needed, our findings suggest the possibility that resilience, optimism, happiness, and low perceived stress might serve as protective factors against insulin resistance and inflammation and their associated negative health outcomes in both schizophrenia and HCs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous studies showing that blood-based biomarkers of inflammation and insulin resistance are related to positive affect/happiness (Matsunaga et al, 2011;Steptoe et al, 2008), well-being (Boehm & Kubzansky, 2012;Osama & Shehab Ael, 2015;Phillips & Perry, 2015;Steptoe et al, 2012), optimism (Ikeda et al, 2011;Roy et al, 2010), psychological resilience or 'hardiness' (Fields, Hoyt, Linnville, & Moore, 2015;Sandvik et al, 2013), and perceived stress (Aschbacher et al, 2013;BarbosaÀLeiker et al, 2014;Shimanoe et al, 2014). Although longitudinal research is needed, our findings suggest the possibility that resilience, optimism, happiness, and low perceived stress might serve as protective factors against insulin resistance and inflammation and their associated negative health outcomes in both schizophrenia and HCs.…”
Section: Discussionsupporting
confidence: 93%
“…insulin resistance) have been associated with PPFs. One study found an increase in psychological well-being and a decrease in homeostasis model assessment-insulin resistance (HOMA-IR) following weight loss in obese patients with type-2 diabetes (Osama & Shehab Ael, 2015). Similarly, a favorable metabolic profile was positively associated with mental health and wellbeing in middle-aged obese individuals (Phillips & Perry, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific reports confirm psychological benefits arising from endurance training in persons with excessive body weight. They concern, inter alia, lowering depression, improved mood and overall self-esteem [26]. Similar effects can also be brought by less intense Pilates training [27] or yoga [28].…”
mentioning
confidence: 99%
“…14,15,16,17,18,19,20,21 . We climax our non-communicable disease (NCD) themes with many articles on diabetes mellitus, rightly so, because this has become such an important disorder in Africa contrary to predictions in the pre-independence colonial era 22,23,24,25 . This is followed by reproductive health issues 26,27,28 ,29,30 , oncology 31,32,33,34 , herbal medicine 35,36,37 , sleep quality 38 and anthropology 39 .…”
mentioning
confidence: 99%